PEMETAAN SEBARAN BIJIH BESI BERDASARKAN KUALITAS DENGAN METODE INVERSE DISTANCE WEIGTHED (IDW) DI DAERAH JORONG PULAKEK KOTO BARU KABUPATEN SOLOK SELATAN - Irfand Irviandha Rafi; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstarct. Indonesia has abundant natural resources, one of which is iron ore. Iron ore is abundant in the islands of Sumatra, Java, Kalimantan, and in several parts of eastern Indonesia. Iron ore is a major mining product in Indonesia, according to the Central Statistics Agency (2016), Indonesia's iron ore production in 2013 was 22,353,337 tons and in 2014 it was 5,951,400 tons. Whether we realize it or not, mining is a very strategic and important sector in supporting Indonesia's economic growth. This research was conducted in the Jorong Pulakek area, Sungai Pagu District, South Solok Regency. The method used in this study was Inverse Distance Weigthed (IDW). In this study, several iron ore exploration activities were carried out including; initial investigation of iron ore (survey and mapping of sampling sites) using GPS with a research area of ± 1300 meters, sampling at several research points ( 10 points) with the characteristics of selecting samples by drilling, then for the distance between sampling points by means of drilling is  10 meters to 15 meters. The spread of iron ore produced by Inverse Distance Wighted estimation using Arcgis shows a filled contour scale which indicates the grade value for each color based on the element, the lowest value is shown in green with a scale value of 8.609-9.89% and the highest value is shown in red. with a scale value of 19.5-21.35%, based on geology the lowest value is shown in green with a scale value of 4.48-5.52% and the highest value is shown in red with a scale value of 12.14-13.1% and based on Oxides the lowest value is shown in green with a scale value of 4.46-5.49% and the highest value is shown in red with a scale value of 12.03-12.98%. The quality of Iron Ore Fe ¬2O3 using XRF tools obtained an average level seen from Element 14.34%, from geology 8.04% and Oxide 7.98%. The results of the mapping of iron ore by quality are of high value and are sustainable.Keywords:.IDW, Bijih Besi, Mapping